Hur översätter man spikning til engelska? Terminologiskt ordboksarbete för högskoleområdet - Holmér, Åsa (LexicoNordica, 2018)
In this paper I discuss how the work of editing a terminological dictionary is done in practice. I focus on the Swedish-English electronic dictionary, which covers terminology in higher education. It has been revised once each year since 2008 by different working groups consisting of both subject specialists and translators. The project is led by me and other terminologists from TNC (the Swedish Centre for Terminology). In the paper I show how a terminological dictionary differs from a lexicographic one and how it provides the opportunity to address certain aspects of concepts, such as the difference between concepts in general language and in language for specific purposes, hierarchies between concepts and equivalence problems between languages.